METHODOLOGY OF ESTIMATING THE POSSIBLE APPLICATION OF SOLAR ENERGY TO PROVIDE CONTINUOUS AIR STANDING PATROL OF HIGH ALTITUDE AIRSHIP OVER THE GIVEN GEOGRAPHICAL POINT - I. E. Kovalev; V. I. Mavritsky; A. V. Redkin; I. N. Kacharava (Научный вестник МГТУ ГА, 2018)
The task solution of optimizing the parameters for an unmanned high-altitude airship and its power system in order to obtain the maximum of air standing patrol duration over a given geographic point requires an effective comparative analysis of the applicability of solar insolation as the main energy source for a power plant under various altitude, latitudinal, seasonal and wind conditions. The availability of a large number of input parameters for designing such a vehicle leads to the conclusion that it is necessary to use the universal specific energy characteristics of a high-altitude airship and its power plant to simplify the analysis and evaluation of technical solutions effectiveness. The main factor determining the power consumption of the power plant is wind flow speed in a given air standing patrol area. It is also known that solar energy is the most affordable source for long-term energy supply. In most cases, the analysis of solutions is reduced to assessing the ratio between the impact of two natural phenomena, solar energy and wind energy, on the high-altitude airship, for this purpose a simplified model of an airship was designed, which can also be applied to a solar energy airplane. In this work, the value of the available and required power per unit of the aircraft mass is selected as the main performance criteria. The available power is determined for any geographical point with the parameters of latitude, altitude and season (day of the year). The required power is determined by the flight altitude, speed and wind direction. Comparing the values of specific characteristics in space-time coordinates, it is possible to perform an effective analysis of the excess or shortage of available solar energy at a given geographical air standing patrol zone, for different altitudes and days of the year. Using the parameters related to aircraft take-off mass, we are also able to define the required dimensionality of the aircraft to carry out continuous aircraft air standing patrol at a given space point.